ANALISIS LAYANAN DAN BAURAN PEMASARAN KLINIK TELEKONSULTASI GIZI RUMAH SAKIT IZZA KARAWANG DI MASA PANDEMI COVID-19 - Wiryawan, Arif Guntur (UI Scholars Hub, 2022)
Izza Karawang Hospital Nutrition Clinic as an excellent service must adapt to the COVID-19 pandemic situation, in this case the transformation into a virtual or Nutrition Teleconsultation Clinic. The Nutrition Teleconsultation Clinic is expected to provide benefits as a means of consulting about healthy diet patterns. The research objective was to analyze the marketing of Nutrition Teleconsultation Clinic services using the STP (Segmenting, Targeting, Positioning) method and the marketing mix with the 4P concept (Product, Price, Place, Promotion). This type of research is quantitative descriptive research. Using primary data collected by questionnaire to 100 respondents, patients who seek treatment at the Izza Hospital Outpatient Installation. The results of the geographic segmentation analysis of Izza Hospital patients are mostly from Karawang Regency (85%), travel time is <30 minutes (67%), and use private vehicles (84%). The demographic segmentation is mostly aged > 50 (41%), female (61%), works taking care of the household (50%). Determining the target of potential customers is patients aged over 20 years with middle economic class.